Lung scar cancer—a reappraisal - McDonnell, L (1981)
A retrospective clinicopathological study of 100 necropsy cases of lung carcinoma revealed three scar cancers. The scarring in a further 11 probably occurred secondary to the tumour. The premise that lung scars initiate malignancy is questioned.